Blinded by the bright: A lack of congruence between colour morphs, phylogeography and taxonomy for a cosmopolitan Indo-Pacific butterflyfish, Chaetodon auriga - Di Battista, Joseph; Waldrop, E.; Rocha, L.; Craig, M.; Berumen, M.; Bowen, B. (Blackwell Publishing, 2015)
Aim: We assess genetic differentiation among biogeographical provinces and colour morphs of the threadfin butterflyfish, Chaetodon auriga. This species is among the most broadly distributed butterflyfishes in the world, occurring on reefs from the Red Sea and western Indian Ocean to French Polynesia and Hawai'i. The Red Sea form lacks a conspicuous 'eye-spot' on the dorsal fin, which may indicate an evolutionary distinction. Location: Red Sea, Indian Ocean and Pacific Ocean. Methods: Specimens were obtained at 17 locations (n = 358) spanning the entire range of this species. The genetic data included 669 base pairs of mitochondrial DNA (mtDNA) cytochrome b and allele frequencies at six microsatellite loci. Analysis of molecular variance, structure plots, haplotype networks and estimates of population expansion time were used to assess phylogeographical patterns. Results: Population structure was low overall, but significant and concordant between molecular markers (mtDNA: ΦST = 0.027, P < 0.001; microsatellites: F ST = 0.023, P < 0.001). Significant population-level partitions were only detected at peripheral locations including the Red Sea and Hawai'i. Population expansion events in the Red Sea and Socotra are older (111,940-223,881 years) relative to all other sites (16,343-87,910 years). Main conclusions: We find little genetic evidence to support an evolutionary partition of a previously proposed Red Sea subspecies. The oldest estimate of population expansion in the Red Sea and adjacent Gulf of Aden indicates a putative refuge in this region during Pleistocene glacial cycles. The finding of population separations at the limits of the range, in the Red Sea and Hawai'i, is consistent with peripheral speciation.